ANALISIS KEBIJAKAN LUAR NEGERI TURKI TERHADAP KERJASAMA TURKI DAN EROPA MENGENAI PENGUNGSI SURIAH - Noermanita, Eka (Global and Policy Journal of International Relations, 2017)
ABSTRACTThe whole influx of Syrian immigrants and refugees, emerge the awareness and building securitization of European Union countries to anticipate the problem by creating cooperation with Turkey through EU-Turkey Joint Action Plan. In through EU-Turkey Joint Action Plan, Turkey will bring the irregular Syrian Refugee in Greek to their territorial and EU will plan to boost financial aid about €1 billion in 2015-2016 period and estimated reach about €3billion at the end of 2018. EU promises to give the visa liberalization and the mst importance is EU will open talks again about Turkey Accession. Furthermore, what EU gives to Turkey is applied as strategy in order to prevent the massive influx of refugees to reach EU countries border. This paper would use the national interest concept, Rational Model Actor (RMA) and Strukturalism to analyze the Turkey immigration policy towards EU-Turkey Joint Action Plan.Keywords: European Union, Turkey, Joint Action Plan, Foreign Policy, Syrian RefugeeDOI : https://doi.org/10.33005/jgp.v5i01.1900